So we define $f:\mathbb{R}\to \mathbb{R}$ and $f(x)=x^2+3x-5$, and we're using the epsilon-delta definition to prove that it is continuous at 3.

So I know the general structure of an epsilon-delta proof, but we were never shown how to prove a nonlinear function. Like I have no idea what to choose delta as, and how to even figure out what we should choose delta as. I know we need to let epsilon be an arbitrary positive real number, and plug the equation so that $|x^2+3x-5-3|<\delta$ so that $|x^2+3x-8|<\delta$. I don't think you can factor this, so what do you do in order to choose delta?

  • $\begingroup$ A $\delta,\epsilon$ proof is to show $|x - a| < \delta \implies |f(x) - f(a) | < \epsilon$. You do not need, use, want, or have $|f(x) -a| < \delta$ which is what you are attempting to use. $(x^2 + 3x-5)$ is $f(x)$ . And $3$ is the $x = a$ value. You don't combine those in any way. You want $|\color{blue}x -3|< \delta \implies |x^2 + 3x -5 -\color{red}{13}|< \epsilon$. And $x^2+3x -5 -13 = x^2 + 3x -18$ which DOES factor if you want to do it by factoring. (You can see my asnwer to see how to avoid factoring altoghether.) $\endgroup$ – fleablood Apr 14 at 19:05

You have that $f(3)=3^2+3\cdot 3-5=13$.

This leads to $|x^2+3x-5-13|=|x^2+3x-18|=|x-3||x+6|$.

Under the assumption that $|x-3|<\delta$ we now have to stipulate $|x+6|$.

The trick is to stipulate. Take some $\delta$. Lets say $\delta=1$ (the value does not matter).

Then $|x-3|<1\Leftrightarrow x-3<1<x+3$. Then $x+6<10$, by just adding 9 to the inequality.

So $|x+6|<10$ when $\delta<1$.

We then get $|x-3||x+6|<10\delta$.

So we have to choose $\delta=\min\{1,\frac{\varepsilon}{10}\}$ to conclude the proof.


Let $\delta$ be the value we want and lets try to find what restrictions we need.

$|x - 3| < \delta$

$3 -\delta < x < 3 + \delta$. As $\delta$ can be arbitrarily small we can assume will always pick a $\delta \le 3$.

$0\le 9-6\delta + \delta^2 < x^2 < 9 +6\delta + \delta^2$

$(9 - 6\delta + \delta^2) + 3(3-\delta) -5 < x^2 + 3x -5 < (9 + 6\delta + \delta^2) + 3(3+\delta) - 5$

$13 - 9\delta + \delta^2 < x^2 +3x-5 < 13 +9\delta + \delta^2$

$-9\delta + \delta^2 < (x^2 + 3x - 5) - 13 < 9\delta + \delta^2$.

now as $\delta$ can be arbitrarily small we can assume we will always pick a $\delta \le 1$. And if $0 < \delta \le 1$ then $\delta^2 \le \delta$.

$9\delta + \delta^2 \le 9\delta + \delta = 10\delta$. And $-9\delta + \delta^2 >-9\delta > -10\delta$.


$-10\delta \le -9\delta + \delta^2 < (x^2 + 3x - 5)-13 <9\delta + \delta^2 < 10 \delta$.


$-10\delta < (x^2 + 3x - 5)-13 < 10 \delta$

$|(x^2 + 3x - 5)-13| < 10\delta$.

$|(x^2 + 3x -5) - (3^3 + 3\cdot 3 - 5)| < 10\delta$

So if we choose a $\delta$ where $\delta \le \frac \epsilon {10}$ and $\delta \le 1$ and $\delta \le 3$ we will be good and proven our result.

So let $\delta = \min(\frac {\epsilon}{10}, 1)$.


It is often the case that the function is monotonous in some neighborhood of the point considered, so that the inequation

$$-\epsilon<f(x)-f(a)<\epsilon$$ can be solved by

$$f^{-1}(f(a)-\epsilon)<x<f^{-1}(f(a)+\epsilon)$$ (or bounds swapped if the function is decreasing).

From this,

$$f^{-1}(f(a)-\epsilon)-a<x-a<f^{-1}(f(a)+\epsilon)-a$$ and


The RHS gives an upper bound for $\delta$.

In more difficult cases, you have to figure out the inverse image of $(f(a)-\epsilon,f(a)+\epsilon)$ and intersect it with an interval of width $2\delta$ centered at $a$.

In practice, it is possible to find shortcuts and gross estimates that fulfill the conditions. Solving the inequalities need not be done in a tight way.

For example, for the limit of $x^2+3x-5$ at $x=3$, we have to achieve $|x^2+3x-18|<\epsilon$. As the slope of the curve is $9$ at the target point, we can try a smaller mutiple, say $\delta=\dfrac{\epsilon}{10}$.

We evaluate

$$\left(3\pm\frac\epsilon{10}\right)^2+3\left(3\pm\frac\epsilon{10}\right)-18=\left(\frac{\epsilon}{100}\pm\frac{9}{10}\right)\epsilon,$$ which is smaller than $\epsilon$ for all $\epsilon<10$.


Another way of looking at it is to rewrite your polynomial as one centered at $x-3$

$$(x-3)^2=x^2-6x+9$$, we are off by $9x$, so we add $9(x-3)$ to get $(x-3)^2 +9(x-3)=x^2+3x-18$. This is off by 13, so we add 13 to get $$(x-3)^2+9(x-3)+13= x^2+3x-5$$, your polynomial. Now you get to see $$|f(x)-f(3)|=|(x-3)^2 +9(x-3)+13-13|=|(x-3)^2+9(x-3)|$$ The advantage of looking at it like this is we can consider how small do we need |x-3| to be to get this under any arbitrary $\epsilon$. Using the triangle inequality, $$|(x-3)^2+9(x-3)|\leq |(x-3)^2|+9|x-3|$$ For numbers where $|a|\leq 1$, squaring preserves the order, so $|x-3|^2\leq |x-3|$ as long as $\delta \leq 1$, and since we get to pick $\delta$, we can make this happen. This simplifies our inequality to

$$|f(x)-f(3)|\leq |x-3|+9|x-3|=10|x-3|$$ so as long as $|x-3|\leq \frac \epsilon {10}$ and 1 at the same time, we are good, so we take the minimum of 1 or $\frac \epsilon {10}$

The general idea here was to reframe your limit as a limit at 0 instead of a limit at 3. Then we can show how close do we need the inputs to be from 0 to keep the outputs close to 0. This works well for functions that near 0 are small, like polynomials.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.